Archiving as Artistic Practice - Batzofin, Jayne (Arts Research Africa, 2022)
This paper looks at the development of an online showcase repository for the ReTAGS (Reimagining Tragedy from Africa and the Global South) practice-as-research artistic productions, Antigone (not quite/quiet) and iKrele leChiza, and the methodology behind documenting and digitally archiving their processes. The paper reflects on the author’s involvement as the digital archivist for the ReTAGS research and the choices made and implemented on the online showcase repository. It considers the strengths and challenges of these archival choices and explores the possibilities of understanding the archive as a means of artistic engagement in its own right.